5G technology: Is it a determinant in the dispute for global economic hegemony between China and the United States in the 21st century? (2021)
The fifth generation (5G) technology is currently the latest manifestation of scientific and technological development in the world, which is impacting the economic, political, and international relations and the national and international security of countries. So far, China has led its implementation, which has lead it to acquire a relevant role in world governance to such an extent that it has given rise to a confrontation with the United States in the context of the dispute for global economic hegemony. The hypothesis of the text is that the progress made by China in 5G technology will be a catalyst for it to be positioned as the first global economic power. The article analyzes the characteristics of 5G technology and its importance in China and the world; it also reviews the race toward technological supremacy, recognizing the role of 5G in the key sectors of China’s economic positioning in the global economy, which will ultimately enable its rise and predominance in the direct battle with the United States.